Analysis of Blockchain Technology in Patient Data Management System : Security, Privacy, and Efficiency in the Digital Healthcare Context - Arsi Yulianjani; Rosdiana Rosdiana; Rizkq Maulansyah Altaufik (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
In the rapidly evolving landscape of digital healthcare, ensuring secure, confidential, and efficient patient data management has become paramount. Blockchain technology has emerged as a promising solution to address these challenges. This study aims to analyze the implementation of blockchain technology within patient data management systems, with a specific focus on security, privacy, and efficiency in the context of digital healthcare. Within this framework, a notable gap arises between technological innovation trends and their practical application within the healthcare sector. This research expands our understanding of how blockchain can be effectively harnessed to tackle security and patient data privacy challenges within the increasingly interconnected digital healthcare environment. Employing a comprehensive methodology that encompasses qualitative and quantitative approaches, including surveys, literature analysis, and case studies, this study delves into how blockchain technology can provide an added layer of security to patient data, enhance privacy through improved access control, and streamline the sharing of health information. The novelty of this research lies in its holistic approach to identifying gaps in blockchain technology application methods within patient data management, while also addressing practical challenges inherent to the digital healthcare context. The anticipated outcomes of this analysis will provide valuable insights for decision-makers aiming to implement blockchain technology to fortify data security, safeguard privacy, and enhance efficiency within patient data management systems. In conclusion, this research contributes to a nuanced comprehension of the potential of blockchain technology to augment security, privacy, and efficiency in patient data management. By shedding light on innovative methods like blockchain integration, this study offers valuable guidance for effectively navigating the dynamic landscape of digital healthcare.